THE MEETING AMONG LOCAL AND GLOBAL LOGICS: BANANA EMPLOYMENT AND TOURISM IN CAHUITA AND PUERTO VIEJO - Molina Alfaro, Eugenia (2013)
This article proposes that there are different types of social logics that determine the development over specific territories or communities. This logic is historical and to understand today the development in Cahuita and Puerto Viejo on the southern Caribbean coast of Costa Rica, among the most important socio-historical logics one must consider the role of production activities, development of communications, employment, migration patterns and tourism expansion. Beginning with the conceptualization of these logics as ways to study the new relationships between the local and the global, the impacts that tourism expansion has had in Cahuita and Puerto Viejo are described and analyzed.